The Importance of Understanding The Basic Concepts of Islamic Religious Education Learning Planning in Improving the Quality of Learning - Susan; Mulyawan Safwandy Nugraha (Zona Education Indonesia, 2023)
The importance of PAI as a subject in education cannot be overstated. Therefore, PAI learning planning is an important activity that will be carried out in the future. Although plans may follow the initial blueprint, unforeseen changes in situations and conditions can lead to deviations. The learning objectives of PAI have been expressly stated in competency standards which include the development and strengthening of faith. This is realized by equipping students with knowledge, appreciation, practice, and experience of Islam, thus giving birth to Muslim individuals who continue to grow in faith, devotion to Allah Subhānahu Wata'ālā, and noble morals in person, society. , national life, and state. These individuals are also equipped to continue their education to a higher level. The purpose of this article is to understand the concept of planning, the basic concepts of Islamic religious education planning in improving the quality of learning. The method used is qualitative using the literature study method. The data collection technique involves reviewing various literature sources, which are sourced from various documents. The results of this study show that planning the implementation of learning activities is very supportive in efforts to improve the quality of education and support an optimal, efficient and effective learning process. The efforts of teachers related to student learning are by preparing learning designs as well as possible such as preparing the syllabus of the Annual Program, Semester Program, LKS, Instruments, Assessment and evaluation